2010
DOI: 10.1021/ic902467h
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic, Photophysical, NMR Spectroscopic and Reactivity Manifestations of the “8-Heteroaryl Effect” in 4,4-Difluoro-8-(C4H3X)-4-bora-3a,4a-diaza-s-indacene (X = O, S, Se) (BODIPY) Systems

Abstract: We have synthesized and fully characterized three novel, yet closely related, heterocyclically meso-substituted (BODIPY) fluorophores 4,4-difluoro-8-(C(4)H(3)X)-4-bora-3a,4a-diaza-s-indacene (X = O, 2-/3-furyl (7/10); Se, 2-selenenyl (9)) through the use of 2-D NMR (COSY, HSQC, and HMBC), single crystal X-ray diffraction, mass spectrometry, elemental analysis, UV-vis spectroscopy, and fluorescent decay lifetimes, for comparison to the previously reported thienyl species (X = S, 2-/3-thienyl (8/11)). Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 58 publications
4
53
1
Order By: Relevance
“…In particular, for the compound 1, the meso-2-furyl ring retains much of orbital coefficient as compared to phenyl ring of compound IV. This is in total contrast to the orbital coefficient pattern of simple meso-2-furyl BODIPY [25] and meso-4-phenyl BODIPY [28] derivatives where the orbital coefficients are majorly located in BODIPY core.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…In particular, for the compound 1, the meso-2-furyl ring retains much of orbital coefficient as compared to phenyl ring of compound IV. This is in total contrast to the orbital coefficient pattern of simple meso-2-furyl BODIPY [25] and meso-4-phenyl BODIPY [28] derivatives where the orbital coefficients are majorly located in BODIPY core.…”
Section: Resultscontrasting
confidence: 62%
“…The structures of the Compounds 1 and IV (Chart 1) were generated in silico by attaching ferrocene moiety to meso-phenyl [28] and meso-2-furyl [25] BODIPY moieties. The structures were energy optimized using quantum mechanics with density functional theory (DFT) [31] and B3LYP [32] gradient corrected correlation functional method in conjugation with ccdzpv**þ basis set [33] and parameters.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the substituent at the 8-position offers another useful method for modifying the absorption and fluorescence properties of BODIPYs. An example of this is the work of Kim et al, detailing the changes in these characteristics observed upon altering the atomic number and position of the chalcogen atom of a heterocyclic substituent [24].…”
Section: Introductionmentioning
confidence: 99%
“…The study of complexes with terminal metal-oxo, sulfido, seleno, and related ligands is an interesting area of inorganic chemistry. This is partly because they are used as reagents and precatalysts [2,3] for organic synthesis and also as models for the active sites in heterogeneous processes. A search in the Cambridge Structural Database (version 5.38, November 2016, plus one update) reveals that the occurrence of terminal chalcogenido complexes diminishes rapidly in the sequence O ≫ S > Se > Te making the oxo complexes the most prevalent.…”
Section: Introductionmentioning
confidence: 99%